THE FUNCTIONS OF ILLOCUTIONARY SPEECH ACTS USED BY TEACHERS IN THE CLASSROOM INTERACTIONS - Armistany, Petra; Zamzani, Zamzani (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2019)
This research aims to describe the functions of illocutionary speech acts used by teachers in learning interactions in class. The research method used in this study is qualitative descriptive. The data collection techniques in this study are observing and taking notes. The source of data in this study is teachers’ speech acts in learning interactions at State Vocational High School (SMK Negeri) 1 Klaten. The data used is the teachers’ oral speech on Mathematics, Science, History, and Accounting subjects in thelearning interactions at SMK Negeri 1 Klaten which has one conception or main idea. According to the results of the study, there are five functions of illocutionary speech acts used by the teacher in the learning interactionsin the class. The five functions include assertive functions in the form of stating and complaining; directive function in the form of commanding and advising; expressive function in the form of greeting and praising; commissive function in the form of promising and offering something; declarative function in the form of giving a name. Of the five functions, directive function is used most frequently, in which the teachers giving more commands.